PRODUCTION AND PROPERTIES OF THE TAU-LEPTON IN E+E- ANNIHILATION AT CM ENERGIES FROM 12-GEV TO 31.6-GEV - Brandelik, R; Braunschweig, W; Gather, K; Kadansky, V; Lubelsmeyer, K; Mattig, P; Martyn, H; Peise, G; Rimkus, J; Sander, H; Schmitz, D; Schultzvondratzig, A; et al. (1980)
We have observed τ production in e+e- annihilation at centre-of-mass energies between 12 and 31.6 GeV with cross sections in agreement with the QED τ-pair cross section. Branching ratios for τ decay have been measured and are consistent with the world averages. We have determined the cutoff parameters of QED Λ+ (Λ-) to be > 73 GeV (82 GeV) and have obtained an upper limit on the τ lifetime of 1.4 × 10-12 s(95% CL). © 1980.